The Impact of Feeding Cannabidiol (CBD) Containing Treats on Canine Response to a Noise-Induced Fear Response Test - Morris, Elizabeth M.; Kitts-Morgan, Susanna E.; Spangler, Dawn M.; McLeod, Kyle R.; Costa, Joao H. C.; Harmon, David L. (Frontiers in Veterinary Science, 2020)
Interest is increasing regarding use of Cannabidiol (CBD) in companion animals due to anecdotal evidence of beneficial behavioral and health effects. The purpose of this investigation was to evaluate the influence of CBD on behavioral responses to fear-inducing stimuli in dogs. Sixteen dogs (18.1 ± 0.2 kg) were utilized in a replicated 4x4 Latin square design with treatments arranged in a 2x2 factorial, consisting of control, 25 mg CBD, trazodone (100mg for 10-20kg BW, 200mg for 20.1-40kg BW), and combination of CBD and trazodone. A fireworks model of noise-induced fear was used to assess CBD effectiveness after 7 d of supplementation. Each test lasted a total of 6 min and consisted of a 3 min habituation phase with no noise and a 3 min noise phase with a fireworks track. Plasma was collected 1 h before, immediately after, and 1 h following testing for cortisol analysis. Behaviors in each 3 min block were video recorded, and heart rate (HR) sensors were fitted for collection of HR and heart rate variability parameters. Research personnel administering treats and analyzing behavioral data were blinded as to the treatments administered. Data were tested for normality using the UNIVARIATE procedure in SAS, then differences examined using the MIXED procedure in SAS with fixed effects of treatment, period, time, and treatment x time interaction. Inactivity duration and HR increased during the first minute of the fireworks track compared with 1 min prior (P < 0.001 and P = 0.011, respectively), indicating the fireworks model successfully generated a fear response. Trazodone lowered plasma cortisol compared with control (P < 0.001), which was attenuated when administered in combination with CBD (P = 0.238). Neither CBD nor trazodone affected the duration of inactivity (P = 0.918 and 0.329, respectively). Trazodone increased time spent with tail relaxed (P = 0.001). CBD tended to increase HR (P = 0.093) and decreased the peak of low- and high-frequency bands (LF and HF, P = 0.011 and 0.022, respectively). These results do not support an anxiolytic effect of CBD in dogs given 1.4 mg CBD/kg BW/d.